STRATEGI PEMBELAJARAN BERBASIS KOGNITIVISME UNTUK MENINGKATKAN PARTISIPASI SISWA DALAM PEMBELAJARAN BAHASA INGGRIS KELAS VII SMP - Fitriah Abubakar; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Student participation in English learning at the junior high school level remains a complex issue because students are required to process vocabulary, sentence structures, meanings, class instructions, and verbal responses within a limited time. Low participation is often understood as shyness or passivity, whereas this condition can also be related to cognitive processes, such as limited working memory, prior knowledge, self-efficacy, and instructional support. This study aims to analyze the participation of seventh-grade students in English language learning from a cognitive perspective, focusing on cognitive load, activation of prior schemas, self-efficacy, learning support, scaffolding, and media use. This research uses a qualitative approach with a case study design. The research subjects consisted of English teachers and seventh-grade junior high school students. Data were collected thru classroom observations, field notes, limited interviews, and documentation. The data were analyzed using thematic analysis by identifying, coding, grouping, and interpreting themes based on the cognitive framework. The research results show that student participation is divided into three patterns: active, reactive, and passive participation. Students who appear silent do not always indicate a lack of interest in learning, but are related to cognitive load, limited vocabulary, underdeveloped initial schemas, varied self-efficacy, and the need for thinking time before responding. These findings indicate that English language learning needs to be designed clearly, gradually, contextually, and supportively to align with students' cognitive capacities and encourage better participation.